2020
DOI: 10.3390/antiox9020148
|View full text |Cite
|
Sign up to set email alerts
|

Lespedeza bicolor Extract Ameliorated Renal Inflammation by Regulation of NLRP3 Inflammasome-Associated Hyperinflammation in Type 2 Diabetic Mice

Abstract: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by hyperglycemia. The chronic hyperglycemic condition causes hyperinflammation via activation of nucleotide-binding oligomerization domain-like pyrin domain containing receptor 3 (NLRP3) inflammasome and abnormally leads to morphological and functional changes in kidney. A previous study showed a protective effect of Lespedeza bicolor extract (LBE) on endothelial dysfunction induced by methylglyoxal glucotoxicity. We aimed to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Chronic hyperglycemia in diabetes promotes a pro-inflammatory state, leading to increased neutrophil counts and subsequent tissue inflammation [ 14 ]. One of the potential mechanisms underlying the association between NLR and proteinuria could be that this chronic inflammation can contribute to immune dysfunction, altered responses to inflammation, renal damage, and ultimately proteinuria [ 15 , 16 ]. Immune dysfunction, characterized by altered neutrophil and lymphocyte counts, may disrupt the immune response against renal injury, thereby facilitating the development of proteinuria [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hyperglycemia in diabetes promotes a pro-inflammatory state, leading to increased neutrophil counts and subsequent tissue inflammation [ 14 ]. One of the potential mechanisms underlying the association between NLR and proteinuria could be that this chronic inflammation can contribute to immune dysfunction, altered responses to inflammation, renal damage, and ultimately proteinuria [ 15 , 16 ]. Immune dysfunction, characterized by altered neutrophil and lymphocyte counts, may disrupt the immune response against renal injury, thereby facilitating the development of proteinuria [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previous study reported by our group found that the Lespedeza bicolor extract (LBE) containing polyphenolic compounds such as quercetin, genistein, daidzein, and naringenin has shown to exert antioxidant and anti-inflammatory effects accompanied by upregulation of the AMPK-SIRT1 pathway in the same diabetic model [52]. The current findings supported that QAE at much lower concentrations compared to LBE and other plant extracts has shown antidiabetic effects through regulation of the AMPK-SIRT related mechanism as shown in LBE treated diabetic mice [52]. Moreover, QAE supplementation attenuated pro-fibrosis as well as apoptosis in the diabetic group, which was not shown in LBE treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests a strong link between diabetic complications and ferroptosis. Hyperglycemia leads to the overproduction of ROS and induces oxidative stress in various organs of diabetic patients (9). High glucose could cause an overload of iron, and iron dysregulation induces the production of ROS and promotes oxidative stress, which leads to ferroptosis finally (10).…”
Section: Introductionmentioning
confidence: 99%